2012
DOI: 10.1371/journal.pone.0047982
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Sustained-Release Formulation of Valproate and Topiramate Monotherapy in Patients with Epilepsy: A Multi-Centre, Cohort Study

Abstract: BackgroundNew-generation antiepileptic drugs (AEDs) tend to replace traditional AEDs as the first-line choice for epilepsy. However, whether this change results in better outcome, especially in China, remains unknown.Methodology/Principal FindingsTwo broad spectrum AEDs, the traditional drug of sustained-release formulation of valproate (SRVPA) and the new-generation drug of topiramate, were compared in patients with epilepsy as monotherapy in this multi-centre, observational cohort study from 2000 to 2011. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 27 publications
2
14
1
Order By: Relevance
“…The proportion of patients whose treatments failed due to lack of efficacy to those their treatments failed due to adverse effect was 4.5:1. This is consistent with a multi-center long-term retrospective study in China [23]. Along with the increase of treatment methods, the incidence of intolerant adverse effect had a downturn trend.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The proportion of patients whose treatments failed due to lack of efficacy to those their treatments failed due to adverse effect was 4.5:1. This is consistent with a multi-center long-term retrospective study in China [23]. Along with the increase of treatment methods, the incidence of intolerant adverse effect had a downturn trend.…”
Section: Discussionsupporting
confidence: 89%
“…Real-world evidence can supplement the content of RCT and has the most promising effectiveness among different treatment strategies [21]. More and more researchers propose that well-designed long-term clinical trials with head-to-head comparisons are required [22][23][24][25]. The American Academy of Neurology and International League Against Epilepsy Commission has recommended more meaningful long-term comparative trials representative of real-world clinical practices [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epilepsy is characterized by the imbalance between excitation and inhibition of central nervous system (CNS) (Engel, 1996 ; Stafstrom, 2003 ), affecting 1–3% of the worldwide population (Bhalla et al, 2012 ). Current prescribed anti-epileptic drugs (AED) are not effective in all individuals with epilepsy (Fu et al, 2009 ; Hu et al, 2012 ), thus it is necessary to find novel therapeutic targets for epilepsy. Previous studies have showed that ion channels play pivotal roles in epilepsy, and most of them have focused on the selective ion channels such as sodium and potassium channels (Armijo et al, 2005 ; Lerche et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Anti-epileptic drugs provide control of seizures in most patients with epilepsy. Nonetheless, current anti-epileptic drugs are only effective in 60-70% of individuals and many drugs can produce numerous unwanted side effects in patients (Hu et al, 2012). For these reasons, novel drugs to treat epilepsy are highly necessary.…”
Section: Introductionmentioning
confidence: 99%